9-Valent human papillomavirus vaccine: a review of the clinical development program - Alain Luxembourg; Erin Moeller (Taylor & Francis Group, 2017)
Introduction: The 9-valent human papillomavirus (9vHPV) vaccine covers the same HPV types (6/11/16/18) as the quadrivalent HPV (qHPV) vaccine and 5 additional cancer-causing types (31/33/45/52/58). Epidemiological studies indicate that the 9vHPV vaccine could prevent approximately 90% of cervical cancers, 70-85% of high-grade cervical dysplasia (precancers), 85-95% of HPV-related vulvar, vaginal, and anal cancers, and 90% of genital warts. Areas covered: Study design features and key findings from the 9vHPV vaccine clinical development program are reviewed. In particular, 9vHPV vaccine efficacy was established in a Phase III study in young women age 16-26 years. Efficacy results in young women were extrapolated to pre- and young adolescent girls and boys and young men by immunological bridging (i.e., demonstration of non-inferior immunogenicity in these groups versus young women). Expert commentary: The development of the 9vHPV vaccine is the outcome of 20 years of continuous clinical research. Broad vaccination programs could help substantially decrease the incidence of HPV-related disease.